Reconfigurable Rectangular Filter With Continuously Tunable Bandwidth and Wavelength - Jiachen Li; Sigang Yang; Hongwei Chen; Minghua Chen (IEEE Photonics Journal, 2020)
We propose and demonstrate a rectangular optical lattice filter with reconfigurable bandwidth and wavelength. The proposed reconfigurable rectangular lattice filter consists of three-stage cascaded ring-assisted Mach-Zehnder interferometers (RAMZIs), and each RAMZI unit serves as an approximate optical elliptical filter with optimized shape factor. The scheme and design principle are presented with the method of zero-pole theory. As a proof of concept, the proposed structure is fabricated on the Si $_3$ N $_4$ waveguide platform. In the experiment, the 3-dB bandwidth of the proposed filter can be continuously tuned from 14.1 GHz to 4.1 GHz, maintaining a rectangular transmission response, and the wavelength can also be continuously tuned. This reconfigurable rectangular optical lattice filter shows the potential in many practical applications for reconfigurable optical signal processing due to flexibility and reconfigurability.